Mental health research capacity building in sub-Saharan Africa: the African Mental Health Research Initiative. (2020) - Chibanda, Dixon; Abas, Melanie; Musesengwa, Rosemary; Merritt, Chris; Sorsdahl, Katherine; Mangezi, Walter; Bandawe, Chiwoza; Cowan, Frances; Araya, Ricardo; Gomo, Exnevia; Gibson, Lorna; Weiss, Helen; et al.
Abstract: Mental, neurological and substance use (MNS) disorders are a leading, but neglected, cause of morbidity and mortality in sub-Saharan Africa. The treatment gap for MNS is vast with only 10% of people with MNS disorders in low-income countries accessing evidence-based treatments. Reasons for this include low awareness of the burden of MNS disorders and limited evidence to support development, adaptation and implementation of effective and feasible treatments. The overall goal of the African Mental Health Research Initiative (AMARI) is to build an African-led network of MNS researchers in Ethiopia, Malawi, South Africa and Zimbabwe, who are equipped to lead high quality mental health research programs that meet the needs of their countries, and to establish a sustainable career pipeline for these researchers with an emphasis on integrating MNS research into existing programs such as HIV/AIDS. This paper describes the process leading to the development of AMARI's objectives through a theory of change workshop, successes and challenges that have been faced by the consortium in the last 4 years, and the future role that AMARI could play in further building MNS research capacity by brining on board more institutions from low- and middle-income countries with an emphasis on developing an evidence-based training curriculum and a research-driven care service.